(untitled) (Colombia Medica, 2024)
Description of the cases: A series of 6 cases with a probable diagnosis of sporadic CJD, treated in a Peruvian national reference hospital, are presented. Clinical findings: The relevant clinical signs were rapidly progressive dementia and myoclonus, followed by akinetic mutism and pyramidal signs. Treatment and results: Of the cases presented, 80% were men, with an average age of presentation of 65 years and a duration from diagnosis to death of 6.5 months. Laboratory tests, images (Brain Resonance), and protein dosage 14.3.3 were performed to support the clinical suspicion. There is no effective treatment for said pathology at the moment. Clinical Relevance: Creutzfeldt-Jakob disease (CJD) is a progressive, fatal, neurodegenerative disease of low prevalence and incidence. Great clinical suspicion and the exclusion of other etiologies are required. Currently, there is no treatment for this entity, and there is a high probability of death before one year.